The Brand Community Journey Into Brand Loyalty of Indonesian Car Owner Community (Case: Pajero Indonesia One) - Nilasari, Irma; Komala Putri, Ratna; Gumilar, Ivan; Taruna, Indra (International Journal of Psychosocial Rehabilitation, 2020)
Brand community as a tool for customer retention strategy is widely accepted by marketing scholars as well as practitioners. The brand community’s affect and trust will influence directly and indirectly brand loyalty via brand community commitment. The present study conducted this framework of thinking with 327 members of PI.One as Pajero owner community in Indonesia as respondents. The factor analysis found that in the PI.One environment, respondents do not differentiate between affect and trust. Thus, the independent variables merged into brand community affect and trust (BCAT). The hypothesis testing found that all hypotheses are supported. Several implications and also future research are discussed at the end of this article.